2019
DOI: 10.1002/lt.25445
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation for Acute Liver Failure: Donor Safety and Recipient Outcome

Abstract: In countries where deceased organ donation is sparse, emergency living donor liver transplantation (LDLT) is the only lifesaving option in select patients with acute liver failure (ALF). The aim of the current study is living liver donor safety and recipient outcomes following LDLT for ALF. A total of 410 patients underwent LDLT between March 2011 and February 2018, out of which 61 (14.9%) were for ALF. All satisfied the King’s College criteria (KCC). Median admission to transplant time was 48 hours (range, 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 49 publications
(149 reference statements)
0
32
0
Order By: Relevance
“…211 Several other studies including 2 Indian reports have shown good outcomes of LDLT for ALF. [212][213][214][215][216] Yamashiki et al 214 reported survival rates of 79%, 74%, and 73% at 1, 5, and 10 years, respectively, in a nationwide survey from Japan. Outcomes of ALF with LDLT and DDLT are similar.…”
Section: Merits Of Various Techniques Of Lt For Alfmentioning
confidence: 99%
“…211 Several other studies including 2 Indian reports have shown good outcomes of LDLT for ALF. [212][213][214][215][216] Yamashiki et al 214 reported survival rates of 79%, 74%, and 73% at 1, 5, and 10 years, respectively, in a nationwide survey from Japan. Outcomes of ALF with LDLT and DDLT are similar.…”
Section: Merits Of Various Techniques Of Lt For Alfmentioning
confidence: 99%
“…With this donor safety policy, we recently reported only 1 major (grade 3a) BC in 410 living donor hepatectomies. (10) The incidence of multiple bile ducts will always be there because it is also associated with biliary anatomy, and almost half of the patients will have a variation. (8,18) With growing experience and the modified technique, the rate of BCs in our series decreased even in the subgroup of patients with multiple ducts.…”
Section: Discussionmentioning
confidence: 99%
“…The posttransplant immunosuppression protocol followed the procedures that have been previously published. (7,9,10) Briefly, it consisted of steroids (100 mg methylprednisolone) in the anhepatic phase, tapered over the next 5 days. Maintenance immunosuppression consisted of tacrolimus plus mycophenolate mofetil plus steroids (prednisolone).…”
Section: Biliary Anastomosismentioning
confidence: 99%
“…A summary of recent publications from tertiary care centers in India is shown in Table 4. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] During epidemics of viral hepatitis,~1% of clinical cases may develop ALF. The various etiologies of ALF include hepatitis virus infections (the most common cause in India), drugs such as anti-TB therapy (ATT) drugs, metabolic causes, ischemia, and toxins.…”
Section: Disease Burdenmentioning
confidence: 99%